Pengaruh Beban Kerja Dan Disiplin Kerja Terhadap Kepuasan Kerja Pegawai Pada Kantor Badan Perencanaan Pembangunan Riset Dan Inovasi Daerah (BAPPERIDA) Kabupaten Mamasa - Dawa, Natsharani Tasik; Nurman; Burhanuddin; Musa, Chalid Imran; Natsir, Uhud Darmawan (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of workload and work discipline on employee job satisfaction at the Regional Development Planning, Research, and Innovation Agency (BAPPERIDA) Office of Mamasa Regency. The type of research used is quantitative with an associative approach, using a questionnaire instrument distributed to 56 active employee respondents. Data were analyzed through multiple linear regression analysis with the help of the SPSS version 27 program. The results of the study indicate that partially workload and work discipline have a positive and significant effect on job satisfaction. Simultaneously, workload and work discipline together have a significant effect on job satisfaction. The coefficient of determination (R²) value is 0.585, which means that 58.5% of the variation in employee job satisfaction is explained by these two variables, while the remaining 41.5% is influenced by other factors outside the model such as the work environment, compensation, and leadership style.